The Relationship between Leptin Levels and Continuous Positive Airway Pressure Treatment: A Cluster Analysis - Oki, Takashi; Kozu, Yutaka; Hoshi, Mamiko; Itoda, Yasunori; Furusho, Naho; Ozoe, Ryosuke; Jinno, Yusuke; Hirata, Akifumi; Kurosawa, Yusuke; Yamada, Shiho; Fukuda, Asami; Hikichi, Mari; Shikano, Sotaro; Sugaya, Kenichi; Hiranuma, Hisato; Maruoka, Shuichiro; Gon, Yasuhiro (Sleep Science, 2024)
Objective Leptin is an appetite-suppressing hormone released by adipose tissue that plays an important role in severe obstructive sleep apnea syndrome (OSAS). However, it is unclear whether leptin levels are a useful biomarker for this syndrome. The present study aimed to assess the effect of continuous positive airway pressure (CPAP) treatment on the syndrome according to leptin levels, using a cluster classification based on clinical features of the syndrome.Materials and Methods We performed a hierarchical cluster analysis of data from 97 OSAS patients diagnosed via polysomnography. We also evaluated the effect after 6 months of CPAP administration.Results Clusters 1 (49 patients; 50.5%) and 2 (6 patients; 6.2%) presented normal leptin levels, and clusters 3 (11 patients; 11.3%) and 4 (31 patients; 32%) presented high leptin levels. Clusters 3 and 4 presented different leptin levels, but the same degree of obesity. After treatment, the levels of excessive daytime sleepiness improved in all clusters. In Cluster 3, leptin levels were significantly reduced after treatment.Conclusion Using the conventional diagnostic method of the apnea-hypopnea index, it was not clear whether leptin is a useful biomarker for the CPAP treatment. However, it may be helpful for particular clusters, including obese women, and where particular populations require CPAP treatment.
Keywords: obstructive sleep apnea; phenotype; cluster analysis; leptin; continuous positive airway pressure